1992
DOI: 10.1177/004051759206200606
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for Predicting Strength Properties of Yarn

Abstract: We present a new approach to yarn characterization and yarn tensile response based on fiber parameters such as strength and strain-at-break, length, and fineness. Yarn characterization is concerned with twist, linear density, and the ratio of experimental yarn unevenness to the Martindale's limit characteristic for spinning mills. Experimental strength results are compared with predicted ones on the basis of theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…15 Many other workers have since followed the examination of fiber and yarn relationships, particularly of yarn strength. [16][17][18][19][20][21][22][23][24] The advent of instruments to measure new aspects of fiber quality, especially from the 1970s with the introduction of HVI lines, meant easier examination of these original relationships. Improved computing power from the 1980s also meant fiber and yarn relationships were defined more in terms of their fit with statistical models, for example, multiple linear regression, principal component analysis and more recently Neural Network or Fuzzy Logic models.…”
Section: Yarn Quality Prediction Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Many other workers have since followed the examination of fiber and yarn relationships, particularly of yarn strength. [16][17][18][19][20][21][22][23][24] The advent of instruments to measure new aspects of fiber quality, especially from the 1970s with the introduction of HVI lines, meant easier examination of these original relationships. Improved computing power from the 1980s also meant fiber and yarn relationships were defined more in terms of their fit with statistical models, for example, multiple linear regression, principal component analysis and more recently Neural Network or Fuzzy Logic models.…”
Section: Yarn Quality Prediction Modelsmentioning
confidence: 99%
“…Theory and empirical evidence [16][17][18][19][20][21][22][23] have long shown that yarn tenacity is primarily but not solely determined by fiber tenacity . Figures 8(a) and (b) show the strong correlations observed between cotton fiber tenacity and yarn tenacity for Datasets 1 and 2.…”
Section: Yarn Tenacitymentioning
confidence: 99%
“…The performance of the ANN was assessed using the root mean of fibers, yarns, and fabrics, the prediction of yarn strength by Frydrych [12], and works performed by Vitro et al, [13] Kim and El-sheikh [14] and Yong Ku Kim [15] and El-sheikh [16] can be mentioned. However, statistical regression models for this purpose have been used by some researchers, namely El-Mogahzy [17], Hunter [18] and Alsaid Ahmed Almetwally [19,20] and M M Mourad [21].…”
Section: Performance Of the Neural Networkmentioning
confidence: 99%
“…Treloar and Riding (1963) used strain energy approach and interpreted the tensile properties of twisted filament yarn in terms of their geometrical structure and the properties of constituent filaments. Fredrych (1992) has predicted the tensile response of cotton yarns by incorporating the migrating properties of the fibres. Onder and Baser (1996) have investigated the stress-strain and breakage behaviour of staple yarn based on conical helix model of fibre migration.…”
Section: Introductionmentioning
confidence: 99%